Akselerasi Tata Kelola BUMDes dalam Perspektif Reinventing Government: Study Komparatif antara BUMDes Pedesaan dan Perkotaan - Petronela Desi Gamda; I Nyoman Subanda; Sahri Aflah Ramadiansyah; Ni Ketut Arniti (Lembaga Pengembangan Kinerja Dosen, 2026)
Village-Owned Enterprises (BUMDes) are a strategic instrument in promoting village economic independence and increasing Village Original Income (PAD). However, in practice, BUMDes management still faces various governance issues, particularly related to human resource capacity, business innovation, and public accountability and trust. This study aims to analyze the acceleration of BUMDes governance from a Reinventing Government perspective through a comparative study between BUMDes in rural and urban areas. This study uses a qualitative method with a descriptive-comparative approach. Data collection techniques are carried out through in-depth interviews, observation, and documentation. The research locations include BUMDes in Paan Leleng Village, Kota Komba Utara District, East Manggarai Regency as a representative of rural villages, and BUMDes in Golo Bilas Village, Komodo District, West Manggarai Regency as a representative of urban villages. The research results indicate that the implementation of Reinventing Government principles in the governance of Village-Owned Enterprises (BUMDes) in both villages has been successful, but not yet optimal. The BUMDes in Golo Bilas Village has advantages in market access, business potential, and innovation, but still faces challenges in accountability and public trust. Meanwhile, the BUMDes in Paan Leleng Village demonstrates strong community participation and social values, but is hampered by limited human resources, technology, and business diversification. Accelerating BUMDes governance requires institutional strengthening, increased managerial capacity, business innovation, and the implementation of governance that is oriented towards results and community needs.